Steganography application for x-ray image of the transferred patient using least significant bit method - Nur Shazana, Matri (2019)
Nowadays, internet seems to be really important since it is one of the most effective ways to communicate. The growth of data transmitting over the internet helps healthcare management for easy access and distribution of patient’s information. However, the patient’s information that being transferred is exposed to the third party and they can easily use or manipulated the information. In this project, an image steganography method using spatial domain techniques is proposed to hide the patient’s information into their medical image for transmission purposed. Using the most popular techniques in spatial domain, Least Significant Bit technique, we replaced the least significant bit of the cover image with the data bit. The proposed method is applied only to X-ray image of the patient. Once the proposed method is adapted and applied in this project, the results indicated that the high quality of the stego-image after the process is achieved.